BAGAIMANA MENGENALKAN DIALEK KEPADA PEMBELAJAR BAHASA INGGRIS - Agus Hari Wibowo; Riyadi Santosa; Tri Wiratno; Djatmika Djatmika (Prasasti: Journal of Linguistics, 2021)
The article discusses how variations of English are introduced to teenage Indonesian English learners through coursebooks for students of high schools. English language units representing such vatiants were collected from five coursebooks for high schools. The collected units were then analysed to see what English variations they are representing, such as British, American, or mixed variaiton, or Indonesian Engish. The results show that the English variations due to its users are represented either in grammar and lexical choices. The latter dominate the numbers of data in showing the variations. The language units representing the variations are presented mostly in dialogs in the forms of utteracances. In addition choice of single words also contribute the representation of the variations. Formality becomes the main feature to differentiate between British and Amerian dialects presented in the books, and introducing English dialects to students through the coursbooks is good in accordance to the fact that recognizing dialects of English will broaden their linguistic knowledge on such a language they are learning.